The Italian Multicentric Study on Legionnaires’ disease (Italian Journal of Public Health, 2004)
The general objective of the Italian Multicentric Study on Legionnaires’ disease is the investigation of some of the critical aspects of this emerging disease, with a specific interest in the Italian situation.An epidemiological study is being conducted in different Italian localities to evaluate the diffusion of Legionella spp in the environment and the efficiency of some of the control strategies to detect cases, study their related risk factors and to establish the frequency of infection within groups at different exposure levels.The first results obtained from the research project are presented below.